EDUCATION FOR THE PREVENTION OF POOR NUTRITION AT TUGU ELEMENTARY SCHOOL - vanya salsabila khairunnisa; Asep Bayu Nandiyanto (Lentera Karya Edukasi, 2022)
The purpose of this study was to provide education regarding the prevention of malnutrition in early childhood at Tugu Elementary School, Cihideung Village, Parongpong, Indonesia. The method used is a qualitative descriptive study, which describes the situation in the field with social activities by providing educational insight on the theme entitled prevention of malnutrition at an early age. This research was conducted on 18 3rd grade students of Tugu Elementary School, Cihideung Village, Parongpong, Indonesia. With an age range of 8-9 years. Respondents consisted of 8 boys and 10 girls. This research was conducted through 3 stages, namely (1) pre-test; (2) providing education through learning media; and (3) post-test. The results obtained from this study there is a change in children's habits in consuming nutritious foods that contain carbohydrates or protein. And it can also be seen from the results of the pre-test and post-test that there is an increase in each statement given. With this research, it is hoped children can sort and choose nutritious foods or not and also with this research, it is expected to reduce the problem of malnutrition.